Akad/Kontrak Dalam Keuangan Syariah, Studi Analisis Terhadap Akad Ijarah Multijasa Pada BMT Al Falah Cirebon - Abdul Aziz; Dede Abdurohman (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
The purpose of this study is to examine the implementation of multi-service ijarah contracts at BMT Al Falah Cirebon, with an emphasis on the implementation of contracts in the field. The main focus of this study examines the relationship between DSN-MUI Fatwa No.44/DSN-MUI/VIII/2004 concerning Multi-Service Financing and practices in the field, including the potential for sharia deviations that can harm members. Qualitative approach with case study methods. Data collection techniques are through direct observation, review of contract and regulatory documents, and literature studies. The results of the study show that the implementation of the multi-service ijarah contract at BMT Al Falah has met the basic principles of sharia, including the clarity of the object of the contract, the determination of ujrah in a fixed nominal form, and the separation of the wakalah contract. Although it was found that the public's understanding of the contract is passive which has the potential to weaken the principle of ikhtiyari in the contract, the BMT tries to explain each article in the contract to members, so that the essence of the principle of ikhtiyari is maintained. The use of the Religious Court as a dispute resolution is in line with the provisions of national law. Practically, these findings contribute to the development of multi-service contracts that are more fair, participatory, and in line with sharia economic law. Further research is suggested to further examine the role of parties in the contract negotiation process and how sharia values are internalized in financing practices.